Business and corporation engagement with higher education : models, theories, and best practices - Clevenger, Morgan R., 1969-; MacGregor, Cynthia J. (Cynthia Jane), 1962- (Emerald Publishing Limited, 2019)
This book further explores the behavior aspects of corporate-higher education inter-organizational relationships by culminating various theories and models addressing the space where U.S. corporations and American higher education intersect. Examples are provided regarding the attraction, motivations, and maintenance needed for higher education to create win-win relationships with businesses. This work offers a new approach to the corporate citizenship literature by providing a broad, holistic review of frameworks to understand the range of motives and expectations of corporate engagement in the American society as evidenced by inter-organizational relationships with higher education. By providing an insight to better design and to manage inter-organizational relationships, this book will prove invaluable to both higher education practitioners and corporations alike.